Wireless Lan For A Library Issues And Challenges - Ketheeswaren, S.; Ashritha, Sr.; Rosaline Mary, S.; Visvanath, B. (Bharathidasan University, 2010)
Wireless LAN is an unguided data communication network within a boundary of place. Wireless communications offer organizations and users with many benefits such as portability and flexibility, increased productivity, and lower installation costs. This paper covers many concerns of the Emerging Wireless Technologies, classification of Wireless LAN, Emerging Benefits of Wireless Technology in Higher Education, Critical challenges of a Wireless LAN and needed wireless LAN Securities. This paper generally discusses the problems freshly emerged from wireless LAN when replacing the wireless LAN in the place of wired LAN and discusses the alternatives to the problems as well.
Keywords: Wireless LAN; Wireless Data Communication; Unguided media